Response to: Students' participation in collaborative research should be recognised. (April 2017) - Bell, Chris; Hall, Benjamin; Hackett, James
Highlights: Involvement as a collaborative author on large studies is no guarantee of academic excellence. Smaller research studies still have a benefit both to patients and the budding researcher. A change to FPAS as suggested by STARsurg might be desirable under a more widespread redesign.